Effect of whole body vibration frequency on neuromuscular activity in ACL-deficient and healthy males - A Giombini; F Menotti; L Laudani; A Piccinini; F Fagnani; A Di Cagno; A Macaluso; F Pigozzi (Termedia Publishing House, 2015)
Whole-body vibration (WBV) has been shown to enhance muscle activity via reflex pathways, thus having the potential to contrast muscle weakness in individuals with rupture of the anterior cruciate ligament (ACL). The present study aimed to compare the magnitude of neuromuscular activation during WBV over a frequency spectrum from 20 to 45 Hz between ACL-deficient and healthy individuals. Fifteen males aged 28±4 with ACL rupture and 15 age-matched healthy males were recruited. Root mean square (RMS) of the surface electromyogram from the vastus lateralis in both limbs was computed during WBV in a static half-squat position at 20, 25, 30, 35, 40 and 45 Hz, and normalized to the RMS while maintaining the half-squat position without vibration. The RMS of the vastus lateralis in the ACL-deficient limb was significantly greater than in the contralateral limb at 25, 30, 35 and 40 Hz (P<0.05) and in both limbs of the healthy participants (dominant limb at 25, 30, 35, 40 and 45 Hz, P<0.05; non dominant limb at 20, 25, 30, 35, 40 and 45 Hz, P<0.05). The greater neuromuscular activity in the injured limb compared to the uninjured limb of the ACL-deficient patients and to both limbs of the healthy participants during WBV might be due to either augmented excitatory or reduced inhibitory neural inflow to motoneurons of the vastus lateralis through the reflex pathways activated by vibratory stimuli. The study provides optimal WBV frequencies which might be used as reference values for ACL-deficient patients.